2015
DOI: 10.1111/mice.12129
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Damage Localization Subsystem Based on Elastic Wave Propagation

Abstract: This article presents an embedded signal processing subsystem constituting a part of a whole structural health monitoring system (SHM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Lamb waves are the most widely used guided ultrasonic waves for damage detection. Large structures, instrumented with low-profile surface-bonded piezoceramic transducers, can be monitored for different types of internal and surface damage with Lamb waves, as illustrated in Lee et al (2003), Na et al (2003), Su et al (2006), Croxford et al (2007), Wandowski et al (2015). Recent years have shown much interest in the third approach.…”
Section: Introductionmentioning
confidence: 99%
“…Lamb waves are the most widely used guided ultrasonic waves for damage detection. Large structures, instrumented with low-profile surface-bonded piezoceramic transducers, can be monitored for different types of internal and surface damage with Lamb waves, as illustrated in Lee et al (2003), Na et al (2003), Su et al (2006), Croxford et al (2007), Wandowski et al (2015). Recent years have shown much interest in the third approach.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the peak frequency of AE signals produced in concrete is below 300 kHz . For different damage modes in concrete, the peak frequencies are also different, so the peak frequency can be used to identify different damage patterns in concrete . This principle also applies to mortar.…”
Section: Resultsmentioning
confidence: 99%
“…AE can be operated continuously, whereas guided waves have to be excited and then recorded after suitable propagation distances (242,336). Guided wave monitoring can also be performed with phased array technology (337) or by looking at reflections from discontinuities or defects with the emitting transducer or with a sensor array around it (338). The application of guided waves and related methods, for example, electromechanical impedance testing, to PMC structures has been reviewed in Ref.…”
Section: Determination Of Structuralmentioning
confidence: 99%